2020
DOI: 10.1177/1708538120902650
|View full text |Cite
|
Sign up to set email alerts
|

Methods and clinical outcomes of in situ fenestration for aortic arch revascularization during thoracic endovascular aortic repair

Abstract: Objective Despite endovascular advances in fenestrated and branched devices, thoracic endovascular aortic repair (TEVAR) for arch pathologies remains challenging. The aim of this study was to provide a contemporary review on the current evidence for in situ fenestration during TEVAR and to evaluate its short- and mid-term clinical outcome in the management of arch pathology. Methods A systematic literature review on in situ fenestration of thoracic aortic stent-graft from January 2003 to September 2018 was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…8,9 Branched stent-grafts have been used with limited experience and acceptable results, but the learning curve can impact operative mortality. 17 TEVAR combined with surgical bypass of the supra-aortic arteries is feasible but usually not considered as the first option for high-risk patients because this hybrid technique increases incisions and the risk of nerve injury and stroke. 2 Three previous reports have shown that ISF appears to be a feasible and effective method for revascularizing the LSA during arch TEVAR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Branched stent-grafts have been used with limited experience and acceptable results, but the learning curve can impact operative mortality. 17 TEVAR combined with surgical bypass of the supra-aortic arteries is feasible but usually not considered as the first option for high-risk patients because this hybrid technique increases incisions and the risk of nerve injury and stroke. 2 Three previous reports have shown that ISF appears to be a feasible and effective method for revascularizing the LSA during arch TEVAR.…”
Section: Resultsmentioning
confidence: 99%
“…2 Three previous reports have shown that ISF appears to be a feasible and effective method for revascularizing the LSA during arch TEVAR. [17][18][19] Three main mechanismsneedle, laser, and radiofrequency-were frequently used, and the short-term results were acceptable, with high success rates and low fenestration-related morbidity. The LSA was the most common aortic branch to receive ISF in the meta-analyzed reports, and most procedures were used in emergent bailout situations.…”
Section: Resultsmentioning
confidence: 99%
“…Although the hybrid procedures already realize the purpose of less trauma, it is preferable to conduct the repair with more endovascular and less open surgery. Recently, the chimney technique and fenestration technique are the most frequently used “off-the-shelf” methods by specialists who treat the aortic arch pathologies ( 15 , 16 ). Moreover, the PMF procedure is more suitable for aortic arch anatomy, with even less rate of endoleak compared with the chimney technique ( 10 , 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of supra‐aortic branches is a major obstacle to TEVAR. Several techniques have been developed to tackle this problem, including debranching, inserting chimney stents, placing branched endografts, and in situ fenestration (ISF) 1,2 . However, debranching techniques are more invasive, the chimney technique increases the risk of endoleak, and branched endografts require custom manufacture, making them more costly and necessitating a long wait time.…”
mentioning
confidence: 99%
“…In contrast, ISF might be a reasonable alternative. It usually involves penetrating the aortic stent graft with a needle, laser, or radiofrequency 1 . Most ISF techniques have used covered stents, with overall good success rates and acceptable short‐term outcomes 2 .…”
mentioning
confidence: 99%